Advances in human factors in simulation and modeling : proceedings of the AHFE 2018 International Conferences on Human Factors and Simulation and Digital Human Modeling and Applied Optimization, held on July 21-25, 2018, in Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA /: proceedings of the AHFE 2018 International Conferences on Human Factors and Simulation and Digital Human Modeling and Applied Optimization, held on July 21-25, 2018, in Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA. (2018) - Unknown
No abstract available